Transgenic foods: NatureÂ´s value vs. market value. - Guzmán, José Lòpez; Miralles, Angela Aparisi (Medicina e Morale, 2001)
In the current debate on transgenic species destined for human consumption, discussion is centered not only on purely technical aspects but also on those of a more diverse nature: environmental demands, patent right issues, consumer protection, farmers' rights, biosecurity, among others. Surely, the ethical requisites for accepting the application of modified DNA techniques on vegetable species should hinge on evaluating the factors of risk and benefit these products pose to human beings. But this is not the only issue to be taken into account. We feel that if the ethical debate on genetically modified organisms is to be adequately brought into focus, it must necessarily be based on a critique previous to the contemporary manipulatory approach to nature and be recognized as having, unlike the latter, a certain inherent value. With such a critique as a point of departure, setting limits on human intervention would be justifiable, so that attitudes which posit nature as a mere object susceptible to undue appropriation would be discouraged. Consequently, applying modified DNA techniques to vegetable species could be deemed acceptable if the final product were shown to be favorable both to humans and to the environment, with no risk of endangering biodiversity. However, it should be pointed out that the absence of risk to the environment and to human beings as a consequence of the cultivation and commercialization of these genetic hybrids has yet to be fully demonstrated. Such a state of affairs calls for precaution. Nor should the issue be reduced to a matter of commercial expediency since economic viability cannot be considered as the most important factor in reaching a final decision. Likewise, control of the new transgenic species cannot be simply delegated to the private sector. Such control is a public affair because it affects living species, and because the possible consequences on the environment and on individual human organisms affect the population as a whole and even future generations. Finally, it is of utmost importance to offer clearer, more straightforward information to the general public on this matter, with less regard to vested interests.